(x的平方+5x+6)分之2+(x的平方+x-6)分之3=(x的平方-4)分之4
1个回答
两边乘(x+2)(x+3)(x-2)
2(x-2)+3(x+2)=4(x+3)
2x-4+3x+6=4x+3
5x+2=4x+3
x=1
经检验,x=1是方程的解
相关问题
通分(2x-4)平方分之x,6x-3x平方分之一,x平方-4分之2x
(x的平方+x分之7)+(x的平方-x分之1)=x的平方-1分之6 (2x-2分之5x+1)+2分之1=3x-3分之4x
[(x的平方-9分之x+3)+(6+x-x的平方分之x)乘(4x-6分之3-x)
x的平方-3x+2分之1 + x的平方-5x+6 + x的平方-4x+3分之1
(2x-4分之x的平方-5x+6)+(x-1分之x的平方-4x+3),其中x=5
4-4x+x的平方分之2x-6除以(x+3)乘3+x分之x的平方+x-6
4-4x+x的平方分之2x-6除以(x+3)乘3-x分之x的平方+x-6
X的平方+4X+4分之X的平方-4Y的平方乘以3x平方+6xy分之x+2
x-3分之x+2乘x的平方-4分之x的平方-6x+9
x的平方+x 分之7+x的平方-x 分之4=x的平方-1 分之6的解